Complex Corrosion Properties of AISI 316L Steel Prepared by 3D Printing Technology for Possible Implant Applications - Hlinka, Josef; Kraus, Martin; Hajnys, Jiri; Pagac, Marek; Petrů, Jana; Brytan, Zbigniew; Tański, Tomasz (Materials (Basel, Switzerland), 2020)
This paper deals with the investigation of complex corrosion properties of 3D printed AISI 316L steel and the influence of additional heat treatment on the resulting corrosion and mechanical parameters. There was an isotonic solution used for the simulation of the human body and a diluted sulfuric acid solution for the study of intergranular corrosion damage of the tested samples. There were significant microstructural changes found for each type of heat treatment at 650 and 1050 °C, which resulted in different corrosion properties of the tested samples. There were changes of corrosion potential, corrosion rate and polarization resistance found by the potentiodynamic polarization method. With regard to these results, the most appropriate heat treatment can be applied to applications with intended use in medicine.
Keywords: corrosion; heat treatment; polarization; additive manufacturing; wettability; implants; biocompatibility